Expectation and duration at the effective lower bound - Thomas B. King (Federal Reserve Bank of Chicago, 2016)
I study unconventional monetary policy in a structural model of risk-averse arbitrage, augmented with an effective lower bound (ELB) on nominal rates. The model exposes nonlinear interactions among short-rate expectations, bond supply, and term premia that are absent from models that ignore the ELB, and these features help it replicate the recent behavior of long-term yields, including event-study evidence on the responses to unconventional policy. When the model is calibrated to long-run moments of the yield curve and subjected to shocks approximating the size of the Federal Reserve.s forward guidance and asset purchases, it implies that those policies worked primarily by changing the anticipated path of short-term interest rates, not by lowering investors.exposures to interest-rate risk. However, the effects of short-rate expectations were more attenuated than the effects of bond-supply shocks during the ELB period.
Keywords: 330